Gore-Tex small-vessel angioplasty: A suitable substitute for the use of autogenous saphenous vein grafts - Garcia-Rinaldi, Raul (1980)
Autogenous saphenous vein has been the material of choice for small-vessel angioplasty and for circulatory access graft reconstruction. In an effort to conserve autogenous saphenous vein, we used expanded polytetrafluoroethylene (PTFE) grafts in 45 patients over a 12-month period. We used Gore-Tex(*) to reconstruct 17 circulatory access grafts, 16 carotid arteries, two brachial arteries, seven femoral arteries, and three popliteal anterior or posterior tibial arteries. The indications for reconstruction were chronic occlusion of the access grafts, trauma to the brachial and anterior tibial arteries, and atherosclerotic disease of the carotid, femoral, and popliteal-tibial arteries. Of the reconstructed circulatory access grafts, one failed immediately because of technical problems in the conduit, and one failed 11 months after reconstruction. All other grafts have functioned well and have produced a marked improvement in flow. Of the 28 patients who underwent reconstruction of arteries measuring 3 mm or less, two had patent arteries but died shortly after operation. The remaining 26 have been followed for one to 43 months. All reconstructed arteries are patent, and there have been no instances of distal embolization or false aneurysm formation. From this brief experience, we conclude that Gore-Tex is a suitable short-term alternative to saphenous vein for small vessel arterioplasty; it also may be the material of choice for reconstructing the outflow tract of occluded access grafts.